2022
DOI: 10.3390/plants11070979
|View full text |Cite
|
Sign up to set email alerts
|

Specific Roles of Lipoxygenases in Development and Responses to Stress in Plants

Abstract: Lipoxygenases (LOXs), naturally occurring enzymes, are widely distributed in plants and animals. LOXs can be non-sulfur iron, non-heme iron, or manganese-containing dioxygenase redox enzymes. LOXs catalyze the oxidation of polyunsaturated fatty acids into fatty acid hydroperoxides. Linolenic acid, a precursor in the jasmonic acid (JA) biosynthesis, is converted to 12-oxo-phytodienoic acid through oxygenation with LOX, allene oxide synthase, and allene oxide cyclase. Moreover, JA participates in seed germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 133 publications
1
30
0
Order By: Relevance
“…LOX exerts multiple functions in higher plants and is considered a biological marker of stress because it mediates the JA biosynthesis [ 5 , 7 , 27 , 28 , 29 ]. The number of LOX isozymes and genes changes depending on the plant species, analyzed organs, and environmental conditions [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LOX exerts multiple functions in higher plants and is considered a biological marker of stress because it mediates the JA biosynthesis [ 5 , 7 , 27 , 28 , 29 ]. The number of LOX isozymes and genes changes depending on the plant species, analyzed organs, and environmental conditions [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…LOXs can be categorized as 9- and 13-lipoxygenases, according to the carbon position (either C9 or C13) where the oxygen is inserted in both C18:2 and C18:3. These enzymes play significant functions in plant development and stress response [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Fatty acids are indispensable components in plant cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect mechanisms include the induction of acquired systematic resistance, plant pathogen molecular patterns (PAMPs) which in turn trigger the immunity and plant resistance proteins (Yu et al, 2022 ). Microorganisms solubilize the phosphorus and zinc, fixing the nitrogen and other macro- and micronutrients which promote the growth of the plants under biotic stress condition by providing nutrition (Singh et al, 2022a ). They also enhance the stress resistance in plants by expressing the gene of phytohormones and stress-related metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…They play important roles in plant development and tolerance to abiotic and biotic stresses (Chen et al, 2022;Mou et al, 2022). LOXs potentially participate in signaling caused by stressor effects and are considered as a stress biomarkers against biotic and abiotic stresses (Singh et al, 2022). Lim et al (2015) reported that CaLOX-overexpressing Arabidopsis plants exhibited tolerance phenotypes to drought and high salt stresses via rapid scavenging of ROS and by inducing high expression of ABA (abscisic acid) and stress-responsive marker genes.…”
Section: Introductionmentioning
confidence: 99%
“…They play important roles in plant development and tolerance to abiotic and biotic stresses ( Chen et al., 2022 ; Mou et al., 2022 ). LOXs potentially participate in signaling caused by stressor effects and are considered as a stress biomarkers against biotic and abiotic stresses ( Singh et al., 2022 ). Lim et al.…”
Section: Introductionmentioning
confidence: 99%